Influencia de la aplicación de estrategias cognitivas en la competencia: Explica el mundo físico en el área de ciencia, tecnología y ambiente en estudiantes del segundo grado de educación secundaria de la Institución Educativa “Simón Bolívar” de Otuzco - 2018 - Rodriguez Rodriguez, Celi Pericles (2019)
ABSTRACT The present investigation had the purpose of applying cognitive strategies to develop the competition: It explains the Physical World, based on Scientific Knowledge of the area of Science Technology and Environment in the students of the second grade of Secondary Education of the Educational Institution "Simón Bolívar" of the city of Otuzco. The research was conducted with a population of 125 students from the four sections A, B, C and D and from which a sample was taken in sections A and B made up of 64 students from the second grade of the "Simón Bolívar" Educational Institution. . Which section "A" made up the experimental group and section "C" the control group. As a data collection instrument that was applied was a Test to measure the level of development of the competition explains the physical world, based on scientific knowledge. As a design, the quasi-experimental with pre and post test was used, at the experimental group and control level, its contrast was made with Student's t-test. The results obtained show that the outstanding achievement level was that the experimental group improved significantly compared to the control group, since this group achieved lower percentages at the post-test level, this improvement is due to the application of cognitive strategies, in the development of the Competence Explains the Physical World, based on scientific knowledge.